Childhood obesity ; associated factors and its relationship with health related quality of life among primary school children in Kuching, Sarawak - Julaidah, Sharip (Universiti Malaysia Sarawak, (UNIMAS), 2010)
The main objective of the study was to determine the factors associated with childhood obesity and the relationship between BMI and HRQOL. It was a cross sectional study conducted among primary school children aged 10-12 years old in Kuching, Sarawak. Height and weight of 380 school children were measured to determine BMI. children were assessed using self reported questionnaire on socio demography and lifestyle pattern